2017
DOI: 10.1007/s10014-016-0276-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of NRAS, PTEN and AKT1 gene mutations in the central nervous system metastases of non-small cell lung cancer

Abstract: Somatic mutations in NRAS, PTEN and AKT1 genes are rarely (~1%) reported in primary NSCLC, but their role in carcinogenesis have been proven. Therefore, we assessed the frequency of them in 145 FFPE tissue samples from CNS metastases of NSCLC using the real-time PCR technique. We identified four (two NRAS and single AKT1 and PTEN) mutations in CNS metastases of NSCLC. All mutations were observed in current male smokers (4% out of the male group; 4/100 and 4.25% out of smokers; 4/94). Three mutations have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In particular, it was discovered that the expression rate of PTEN in NSCLC tissue was lower compared with that in healthy individuals. Thus, it may be hypothesized that PTEN mutations lead to activation of the AKT pathway and inhibition of autophagy, and play a role in tumor initiation and progression ( 27 , 28 ). Similarly, it has been demonstrated that expression of PTEN protein in NSCLC is lower compared with that in healthy individuals, from which it was suggested that PTEN tumor regulation may be mediated through the regulation of autophagy ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was discovered that the expression rate of PTEN in NSCLC tissue was lower compared with that in healthy individuals. Thus, it may be hypothesized that PTEN mutations lead to activation of the AKT pathway and inhibition of autophagy, and play a role in tumor initiation and progression ( 27 , 28 ). Similarly, it has been demonstrated that expression of PTEN protein in NSCLC is lower compared with that in healthy individuals, from which it was suggested that PTEN tumor regulation may be mediated through the regulation of autophagy ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The amplification protocol included the following steps 95 °C for 10 min and 92 °C for 15 s, 58 °C for 1 min. for five cycles, followed by 92 °C for 15 s, 60 °C for 60 s for 40 cycles [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…The design principle for the detection of multiple SNPs has been shown in Scheme . The detection targets are the mutated NRAS genes, which are associated with colorectal cancer, melanoma, and nonsmall-cell lung carcinoma. We expect that this approach can be used to detect the presence of three different sequences containing mutations of NRAS codon 61. Codon 61 is the most common position of NRAS alterations in melanoma, with frequent glutamine changes to either histidine Q61H (c.183A > T), lysine, Q61K (c.181C > A), or arginine, Q61R (c.182A > G) .…”
Section: Resultsmentioning
confidence: 99%
“…After the PCR amplification, 1 μL of Exo I (5 units) was added to digest the unreacted primers for 10 min at 37 °C and inactivated at 85 °C. Then 3 μL of λ exo (5 units) was added to digest the 5′-PO 4 labeled strands in the duplex PCR products for 20 min at 37 inactivated at 85 °C for 10 min. The detection assay was performed as described above using CGE-LIF for readout.…”
mentioning
confidence: 99%